Antioksidan Beluntas - Wijaya, C. Hany; Hardjosworo, Peni Suprapti; Sajuthi, Dondin (UPN VETERAN JAWA TIMUR, 2011)
Beluntas (Pluchea indica Less) is a herb that commonly used as traditional medicine and food. Its leaves have many biological activities, because they contain various phenolic compounds. The phenol concentration of beluntas leaves depends on leaf segment, earth condition, fertilizer and environmental stress. This research is focused to determine antioxidant activity of three groups of beluntas leaf segments that includes 1-3, 4-6 and > 6. They were ground, dried at ambient temperature for 7 days, maserated by petroleum eter (1:4 b/v) at ambient temperature for 24 hours and soxhlet extracted by methanol (1:15 b/v) at 65oC for 3 hours. The result shows that the extract contains phytochemical compounds such as tannin, sterol, phenol hydroquinone and flavonoid. This extract has antioxidant activity to scavenging free radical DPPH (2,2-phenyl-1-picrylhydrazyl). The extract of 1-3 beluntas leaf segment was more potential antioxidant source than 4-6 and > 6 beluntas leaf segments, because it had the least IC50 (inhibitor concentration) and the highest total phenol and total flavonoid. The IC50, total phenol and flavonoid total of it were 3.71 mg/L, 234.65 mg GAE/100 g samples and 2163.59 mg QE/ 100 g samples, respectively.